Search for Resonant Pair Production of Neutral Long-Lived Particles Decaying to b(b)over-bar in p(p)over-bar Collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (Amer Physical Soc, 2009)
We report on a first search for resonant pair production of neutral long-lived particles (NLLP) which each decay to a b (b) over bar pair, using 3.6 fb(-1) of data recorded with the D0 detector at the Fermilab Tevatron collider. We search for pairs of displaced vertices in the tracking detector at radii in the range 1.6-20 cm from the beam axis. No significant excess is observed above background, and upper limits are set on the production rate in a hidden-valley benchmark model for a range of Higgs boson masses and NLLP masses and lifetimes.